Caracterização e otimização de um sistema de aquecimento de água utilizando coletor solar com concentrador cônico - Toniazzo, Fernando (2016)
This work aims to optimize a solar water heating system for use on small farms. The solar heating system to be optimized is based on a collector with conical concentrator. The principle of concentration of light in a solar funnel collector comes down in abstraction and reflection of solar radiation to central hub with a tapered inner faces reflective. The solar energy concentration area is occupied by a receiver with high thermal conductivity material, suitably isolated by transparent surfaces for forming the greenhouse, where thermal energy is transferred to a working fluid. The characterization of the system shall take place with test runs the field to relate the proposed changes as a function of system efficiency. The method is summarized in data sampling in different scenarios, which vary according to the heating system (passive and active) and solar tracking (manual and stationary). Preliminary results show the optimization of the absorber geometry and the interaction of light in a conical concentrator. The results demonstrate that the scenarios with solar tracker have higher efficiency than with fixed orientation and solar heating systems operated actively are more efficient than passive systems